PH-sensitive coaxial nanofiber membrane loaded with enoxacin as well as preparation method and application of pH-sensitive coaxial nanofiber membrane
The pH-sensitive coaxial nanofiber membrane with enofloxacin loading prepared by electrospinning technology solves the problem that existing trauma treatment dosage forms are difficult to target trauma pH changes and bacterial infections, and achieves the precise regulation of drug release and rapid effects of trauma healing.
Patent Information
- Application Number
- CN202411732173.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-28
AI Technical Summary
Existing trauma treatment dosage forms such as tablets, ointments and gels are insufficient, which is difficult to effectively target the pH changes in skin trauma and bacterial infections, and are prone to wound infections and adverse reactions.
Electrospinning technology was used to prepare enofloxacin-loaded pH-sensitive coaxial nanofiber membranes, and nanofiber membranes with core-shell structures formed by ethyl cellulose and Eudragit L100, so as to regulate drug release according to the changes in wound pH.
This nanofiber membrane can accurately regulate drug release in the microenvironment of trauma repair, reduce the risk of sudden drug release, avoid adverse reactions, promote rapid healing of skin trauma, and improve the speed and quality of wound repair.
Smart Images

Figure CN119523876A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pharmaceutical preparations, and in particular relates to a pH-sensitive coaxial nanofiber membrane loaded with enoxacin, and a preparation method and application thereof. Background Art
[0002] As the outermost organ of the human body, the skin is extremely sensitive to trauma. Skin injuries such as burns and scalds can destroy the normal physiological functions and barrier functions of the skin. Among them, deep partial burns are the most common wounds, which destroy the entire epidermis and most of the dermis. The wounds are often difficult to heal and will form severe scars. Human skin has the characteristics of low moisture, acidic pH, high salt and high fat content. The pH value of normal skin is 4-6. When it is traumatized, the pH value will rise to above 6, providing a suitable growth environment for a variety of bacteria. The main direction of clinical treatment at present is to avoid bacterial infection of the wound and absorb the wound exudate in time. The drug-loaded coaxial nanofiber membrane shows good therapeutic effect in deep burns, can effectively promote wound healing, and is a new effective treatment for burns and scalds.
[0003] There are many technologies for preparing nanofiber membranes. Electrospinning provides an easy-to-operate, relatively economical and efficient method for making nanofiber membranes. The basic electrospinning equipment has four common components: a high-voltage power supply, a precision injection pump, a syringe with a metal needle (spinneret) and a collector. Coaxial electrospinning uses a coaxial stainless steel needle with two concentrically arranged channels, each of which is injected with a polymer solution at a separate flow rate through a different syringe. The fibers produced by coaxial electrospinning have a core-shell structure and can achieve multiple functions.
[0004] Enoxacin is a synthetic fluoroquinolone antibiotic with a broad antibacterial spectrum, strong bactericidal effect and low toxicity, and is more economical than antibiotics prepared by fermentation. Enoxacin is a third-generation quinolone antibiotic with strong antibacterial effects on Gram-negative and Gram-positive bacteria (such as Streptococcus, Staphylococcus, Pseudomonas aeruginosa, Escherichia coli, Acinetobacter, Proteus, etc.), and has no obvious cross-resistance with other antibacterial drugs. The antibacterial mechanism of enoxacin is to destroy topoisomerase IV and DNA helicase, thereby inhibiting the synthesis of bacterial nucleic acids and causing the breakage of bacterial chromosomes. Enoxacin is mostly used to treat bacterial infections, and has good effects on bacterial skin infections and soft tissue infections.
[0005] Polyacrylic acid resin (Eudragit L100) is a pH-sensitive material. Eudragit L100 dissolves only when the pH value is above 6, which can achieve the purpose of regulating drug release behavior and wound antibacterial according to changes in wound pH.
[0006] Among the existing patents, CN112824406B discloses an enoxacin propylene ketone derivative and its preparation method and application, and CN100563657C discloses an enoxacin ophthalmic sustained-release gel and its preparation method, which has the characteristics of maintaining effective drug concentration for a long time and good compatibility. At present, propylene ketone derivatives may interact with other drugs, affect drug metabolism and excretion, thereby increasing the risk of adverse reactions or reducing the therapeutic effect. Gel preparations have poor air permeability and are prone to wound infection. Summary of the invention
[0007] In order to solve the inherent shortcomings of the dosage forms such as tablets, ointments, gels, etc. currently used in the field of wound treatment, the purpose of the present invention is to provide a method for preparing a pH-sensitive coaxial nanofiber membrane loaded with enoxacin and its application in tissue wound repair.
[0008] The technical solution adopted by the present invention is: a pH-sensitive coaxial electrospun nanofiber membrane loaded with enoxacin, the electrospun nanofiber membrane consists of a shell layer and a core layer, the shell layer contains ethyl cellulose and Eudragit L100, the core layer contains ethyl cellulose and enoxacin, and is made by electrospinning technology.
[0009] The above-mentioned method for preparing a pH-sensitive electrospun nanofiber membrane loaded with enoxacin comprises the following steps:
[0010] 1) Dissolve ethyl cellulose EC and Eudragit L100, stir evenly, and remove bubbles by ultrasound to obtain a shell solution;
[0011] 2) Dissolve ethyl cellulose EC and the raw material drug enoxacin in methanol, stir evenly, and remove bubbles by ultrasound to obtain a core layer solution;
[0012] 3) The shell layer solution and the core layer solution are respectively loaded into two syringes, and a coaxial needle is installed, and the positive high voltage contact clip is connected to the metal needle, and the negative high voltage contact clip is connected to the receiver, and the aluminum foil fixed on the receiver is used as a receiving device, and the power supply, spinning distance, and spray speed are controlled, and a pH-sensitive coaxial electrospinning nanofiber membrane loaded with enoxacin having a core-shell structure is prepared by electrospinning technology;
[0013] 4) The obtained pH-sensitive coaxial electrospun nanofiber membrane loaded with enoxacin was dried in a light-proof vacuum to remove the residual solvent.
[0014] In the above preparation method, in step 1), the shell solution has an ethyl cellulose EC concentration of 8% and an Eudragit L100 concentration of 15%.
[0015] In the above-mentioned preparation method, in step 2), the core layer solution has an ethyl cellulose EC concentration of 2-8% and an enoxacin concentration of 5.00-7.00 μg·mL -1 .
[0016] In the above preparation method, in step 2), the core layer solution has an ethyl cellulose EC concentration of 4% and an enoxacin concentration of 6.00 μg·mL -1 .
[0017] In the above preparation method, in step 3), the volume ratio of the core layer solution to the shell layer solution is 1:1-4.
[0018] In the above preparation method, in step 3), the volume ratio of the core layer solution to the shell layer solution is 1:1.
[0019] In the above preparation method, in step 3), the needle for the core layer solution is No. 22, and the needle for the shell layer solution is No. 17.
[0020] In the above-mentioned preparation method, in step 3), the conditions of the electrospinning technology are: the positive voltage is 14 kV, the negative voltage is 1 kV, the distance between the needle tip and the receiving device is 10 cm, the ambient temperature is 25±5°C, the ambient humidity is 30±10%, and the injection speed of the core layer / shell layer injection pump is 0.03 / 0.09 mm / min.
[0021] The above-mentioned pH-sensitive coaxial electrospun nanofiber membrane loaded with enoxacin is used as a wound dressing.
[0022] The present invention has the following beneficial effects:
[0023] 1. The pH-sensitive coaxial electrospun nanofiber membrane prepared by the present invention has a dosage form prepared by traditional preparation methods, which can overcome various drawbacks, and can be more targeted and effective than tablets, powders, etc., and reduce the dosage. Compared with ointments, gels, etc., it can form an effective barrier to protect the tissue wound surface, and can ensure that the active ingredients of the drug are not affected and can control their release, improve bioavailability, and at the same time ensure a relatively moist environment in the affected area, accelerating the growth of tissue repair cells.
[0024] 2. The present invention uses pH-sensitive material Eudragit L100 to prepare the nanofiber shell layer. Eudragit L100 dissolves only when the pH value is above 6, which can achieve the purpose of regulating drug release behavior and wound antibacterial according to changes in wound pH value.
[0025] 3. In the present invention, the coaxial electrospinning technology is used to prepare the pH-sensitive enoxacin nanofiber membrane, which dynamically responds to the pH changes during the skin wound repair process, thereby regulating the drug release behavior. At the same time, in the wound repair microenvironment, the pH-sensitive coaxial nanofiber membrane can accurately regulate the proliferation of skin cells and the expression of corresponding cytokines, effectively promoting the repair of skin wounds.
[0026] 4. In the present invention, the coaxial electrospun nanofiber membrane can provide a three-dimensional cell scaffold to provide support for cell migration and growth, so that more cell growth and adhesion factors are released, accelerating the tissue healing process.
[0027] 5. In the present invention, enoxacin is a synthetic fluoroquinolone antibacterial drug with a broad antibacterial spectrum, strong bactericidal effect and low toxicity. Since the fibers are all nano-scale structures, the drug can be smoothly dispersed evenly, avoiding adverse reactions caused by excessive local drug concentration.
[0028] 6. The pH-sensitive coaxial electrospun nanofiber membrane prepared by the present invention can ensure that the drug takes effect smoothly. It can be used as a new drug delivery system for tissue trauma, which can reduce the sudden release of drugs, load the drugs evenly, and release them in a controllable manner, thereby ensuring that the drugs in the wound can take effect continuously and accelerate the healing process.
[0029] 7. The present invention uses electrospinning technology to prepare continuous nanofibers, organically combining the commonly used technology in the field of materials with the preparation method, and spinning ethyl cellulose (EC) and the raw material enoxacin in the fiber core layer, and spinning the shell material and Eudragit L100 in the shell layer. With the help of the high specific surface area and porosity of the fiber membrane, a mesh space structure is formed, which helps to absorb the exudate and maintain a relatively moist environment at the wound site. At the same time, it imitates the extracellular matrix structure and promotes the proliferation and migration of cells required for wound repair. Through reasonable preparation design, the prepared drug-loaded nanofiber membrane is non-cytotoxic and has good biocompatibility. At the same time, the nanofiber membrane can also promote the proliferation of fibroblasts, improve the speed and quality of wound repair, and has a relatively good effect and process of promoting wound healing. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 SEM images of the electrospun nanofiber membranes prepared in Example 1(a) and Comparative Example 1.1(b), Comparative Example 1.2(c), and Comparative Example 1.3(d).
[0031] Figure 2 Electron microscope images of the nanofiber membranes prepared at different voltages in Example 1(a) and Comparative Example 1.4(b), Comparative Example 1.5(c), and Comparative Example 1.6(d).
[0032] Figure 3 (a) is a SEM image of the nanofiber membrane of Example 1 that was taken out and dried after being released in a phosphate buffer solution with a pH value of 7.4 for 48 hours, and the corresponding fiber diameter distribution histogram (b).
[0033] Figure 4 TEM images of the coaxial nanofiber membranes prepared in Example 1: (a) a shell diameter of 647 nm and a core diameter of 220 nm; (b) a shell diameter of 635 nm and a core diameter of 208 nm.
[0034] Figure 5 This is a graph showing the release results of the coaxial nanofiber membrane prepared in Example 1 in buffer solutions of five pH values.
[0035] Figure 6 This is a graph showing the experimental results of water vapor permeability of the coaxial nanofiber membrane prepared in Example 1.
[0036] Figure 7 This is a graph showing the water absorption results of the fiber membrane prepared in Example 1 at various time points.
[0037] Figure 8 (a) shows three different wound dressings and a blank control group. Photos were taken on the 1st, 4th, 8th, 14th and 21st days to record the wound area. The red part in (b) is the wound area, and the green part is the healed wound area. (c) is a histogram of the wound area.
[0038] Figure 8-1 The Masson staining images of Example 1 and the control group after wound healing.
[0039] Fig. 9 (a) is the VEGF immunohistochemistry results of three different wound dressings and a blank control group, taken on days 8 and 21; (b) is a histogram of the VEGF immunohistochemistry results.
[0040] Fig.10 (a) is the CD31 immunohistochemistry results of three different wound dressings and a blank control group, taken on days 8 and 21; (b) is a histogram of the CD31 immunohistochemistry results. DETAILED DESCRIPTION
[0041] Example 1
[0042] A pH-sensitive coaxial nanofiber membrane loaded with enoxacin, the preparation method comprising the following steps:
[0043] 1. Weigh an appropriate amount of ethyl cellulose (EC), add methanol, stir to dissolve, and prepare an ethyl cellulose (EC) solution with a concentration of 8% (w / v%). Weigh an appropriate amount of Eudragit L100, mix it with the fixed ratio ethyl cellulose (EC) solution to make its concentration 15% (w / v%), stir to dissolve, and obtain a uniform solution as the shell solution for spinning.
[0044] In the obtained shell solution, the concentration of ethyl cellulose (EC) is 8% (w / v%) and the concentration of Eudragit L100 is 15% (w / v%) by mass volume percentage.
[0045] 2. Weigh an appropriate amount of ethyl cellulose (EC) and the raw material enoxacin and add them to methanol. Stir on a magnetic stirrer until they are completely dissolved to prepare an EC solution with a concentration of 4% (w / v%) as the core layer solution.
[0046] In the obtained core layer solution, the concentration of ethyl cellulose (EC) was 4% (w / v%) and the concentration of enoxacin was 6.00 μg·mL -1 .
[0047] 3. According to the volume ratio of core layer solution to shell layer solution of 1:1, the shell layer solution and core layer solution were respectively loaded into two 10mL syringes, and coaxial needles were installed. The core layer needle selected here was No. 22, and the shell layer needle was No. 17. The positive high-voltage contact clip was connected to the metal needle, and the negative high-voltage contact clip was connected to the receiver. The aluminum foil fixed on the receiver was used as the receiving device. The power supply, spinning distance, spray speed and other parameters were controlled. Through the electrospinning technology, a pH-sensitive electrospinning nanofiber membrane loaded with enoxacin with a core-shell structure was prepared.
[0048] The conditions of the electrospinning technology are: positive voltage of 14 kV, negative voltage of 1 kV, the distance between the needle tip and the receiving device is 10 cm, the ambient temperature is 25±5°C, the ambient humidity is 30±10%, and the injection speed of the core / shell injection pump is 0.03 / 0.09 mm / min.
[0049] 4. The obtained pH-sensitive nanofiber membrane loaded with enoxacin was dried in a light-proof vacuum to remove the residual solvent.
[0050] Comparative Example 1.1
[0051] A pH-sensitive coaxial nanofiber membrane loaded with enoxacin, the preparation method comprising the following steps:
[0052] 1. Weigh an appropriate amount of ethyl cellulose (EC), add methanol, stir to dissolve, and prepare an ethyl cellulose (EC) solution with a concentration of 8% (w / v%). Weigh an appropriate amount of Eudragit L100, mix it with the fixed ratio ethyl cellulose (EC) solution to make its concentration 15% (w / v%), stir to dissolve, and obtain a uniform solution as the shell solution for spinning.
[0053] In the obtained shell solution, the concentration of ethyl cellulose (EC) is 8% (w / v%) and the concentration of Eudragit L100 is 15% (w / v%) by mass volume percentage.
[0054] 2. Weigh an appropriate amount of ethyl cellulose (EC) and the raw material enoxacin and add them to methanol. Stir on a magnetic stirrer until they are completely dissolved to prepare an EC solution with a concentration of 2% (w / v%) as the core layer solution.
[0055] In the obtained core layer solution, the concentration of ethyl cellulose (EC) was 2% (w / v%) and the concentration of enoxacin was 6.00 μg·mL -1 .
[0056] 3. According to the volume ratio of core layer solution to shell layer solution of 1:1, the shell layer solution and core layer solution were respectively loaded into two 10mL syringes, and coaxial needles were installed. The core layer needle selected here is No. 22, and the shell layer needle is No. 17. Connect the positive high-voltage contact clip to the metal needle, connect the negative high-voltage contact clip to the receiver, and use the aluminum foil fixed on the receiver as the receiving device to control the power supply, spinning distance, spray speed and other parameters. Through electrospinning technology, a pH-sensitive electrospinning nanofiber membrane loaded with enoxacin with a core-shell structure was prepared.
[0057] The conditions of the electrospinning technology are: positive voltage of 14 kV, negative voltage of 1 kV, the distance between the needle tip and the receiving device is 10 cm, the ambient temperature is 25±5°C, the ambient humidity is 30±10%, and the injection speed of the core / shell injection pump is 0.03 / 0.09 mm / min.
[0058] 4. The obtained pH-sensitive nanofiber membrane loaded with enoxacin was dried in a light-proof vacuum to remove the residual solvent.
[0059] Comparative Example 1.2
[0060] A pH-sensitive coaxial nanofiber membrane loaded with enoxacin, the preparation method comprising the following steps:
[0061] 1. Weigh an appropriate amount of ethyl cellulose (EC), add methanol, stir to dissolve, and prepare an ethyl cellulose (EC) solution with a concentration of 8% (w / v%). Weigh an appropriate amount of Eudragit L100, mix it with the fixed ratio ethyl cellulose (EC) solution to make its concentration 15% (w / v%), stir to dissolve, and obtain a uniform solution as the shell solution for spinning.
[0062] In the obtained shell solution, the concentration of ethyl cellulose (EC) is 8% (w / v%) and the concentration of Eudragit L100 is 15% (w / v%) by mass volume percentage.
[0063] 2. Weigh an appropriate amount of ethyl cellulose (EC) and the raw material enoxacin and add them to methanol. Stir on a magnetic stirrer until they are completely dissolved to prepare an EC solution with a concentration of 6% (w / v%) as the core layer solution.
[0064] In the obtained core layer solution, the concentration of ethyl cellulose (EC) was 6% (w / v%) and the concentration of enoxacin was 6.00 μg·mL -1 .
[0065] 3. According to the volume ratio of core layer solution to shell layer solution of 1:1, the shell layer solution and core layer solution were respectively loaded into two 10mL syringes, and coaxial needles were installed. The core layer needle selected here was No. 22, and the shell layer needle was No. 17. The positive high-voltage contact clip was connected to the metal needle, and the negative high-voltage contact clip was connected to the receiver. The aluminum foil fixed on the receiver was used as the receiving device. The power supply, spinning distance, spray speed and other parameters were controlled. Through the electrospinning technology, a pH-sensitive electrospinning nanofiber membrane loaded with enoxacin with a core-shell structure was prepared.
[0066] The conditions of the electrospinning technology are: positive voltage of 14 kV, negative voltage of 1 kV, the distance between the needle tip and the receiving device is 10 cm, the ambient temperature is 25±5°C, the ambient humidity is 30±10%, and the injection speed of the core / shell injection pump is 0.03 / 0.09 mm / min.
[0067] 4. The obtained pH-sensitive nanofiber membrane loaded with enoxacin was dried in a light-proof vacuum to remove the residual solvent.
[0068] Comparative Example 1.3
[0069] A pH-sensitive coaxial nanofiber membrane loaded with enoxacin, the preparation method comprising the following steps:
[0070] 1. Weigh an appropriate amount of ethyl cellulose (EC), add methanol, stir to dissolve, and prepare an ethyl cellulose (EC) solution with a concentration of 8% (w / v%). Weigh an appropriate amount of Eudragit L100, mix it with the fixed ratio ethyl cellulose (EC) solution to make its concentration 15% (w / v%), stir to dissolve, and obtain a uniform solution as the shell solution for spinning.
[0071] In the obtained shell solution, the concentration of ethyl cellulose (EC) is 8% (w / v%) and the concentration of Eudragit L100 is 15% (w / v%) by mass volume percentage.
[0072] 2. Weigh an appropriate amount of ethyl cellulose (EC) and the raw material enoxacin, add them to methanol, stir on a magnetic stirrer until they are completely dissolved, and prepare an EC solution with a concentration of 8% (w / v%) as the core layer solution.
[0073] In the obtained core layer solution, the concentration of ethyl cellulose (EC) was 8% (w / v%) and the concentration of enoxacin was 6.00 μg·mL -1 .
[0074] 3. According to the volume ratio of core layer solution to shell layer solution of 1:1, the shell layer solution and core layer solution were respectively loaded into two 10mL syringes, and coaxial needles were installed. The core layer needle selected here was No. 22, and the shell layer needle was No. 17. The positive high-voltage contact clip was connected to the metal needle, and the negative high-voltage contact clip was connected to the receiver. The aluminum foil fixed on the receiver was used as the receiving device. The power supply, spinning distance, spray speed and other parameters were controlled. Through the electrospinning technology, a pH-sensitive electrospinning nanofiber membrane loaded with enoxacin with a core-shell structure was prepared.
[0075] The conditions of the electrospinning technology are: positive voltage of 14 kV, negative voltage of 1 kV, the distance between the needle tip and the receiving device is 10 cm, the ambient temperature is 25±5°C, the ambient humidity is 30±10%, and the injection speed of the core / shell injection pump is 0.03 / 0.09 mm / min.
[0076] 4. The obtained pH-sensitive nanofiber membrane loaded with enoxacin was dried in a light-proof vacuum to remove the residual solvent.
[0077] Comparative Example 1.4
[0078] A pH-sensitive coaxial nanofiber membrane loaded with enoxacin, the preparation method comprising the following steps:
[0079] 1. Weigh an appropriate amount of ethyl cellulose (EC), add methanol, stir to dissolve, and prepare an ethyl cellulose (EC) solution with a concentration of 8% (w / v%). Weigh an appropriate amount of Eudragit L100, mix it with the fixed ratio ethyl cellulose (EC) solution to make its concentration 15% (w / v%), stir to dissolve, and obtain a uniform solution as the shell solution for spinning.
[0080] In the obtained shell solution, the concentration of ethyl cellulose (EC) is 8% (w / v%) and the concentration of Eudragit L100 is 15% (w / v%) by mass volume percentage.
[0081] 2. Weigh an appropriate amount of ethyl cellulose (EC) and the raw material enoxacin and add them to methanol. Stir on a magnetic stirrer until they are completely dissolved to prepare an EC solution with a concentration of 4% (w / v%) as the core layer solution.
[0082] In the obtained core layer solution, the concentration of ethyl cellulose (EC) was 4% (w / v%) and the concentration of enoxacin was 6.00 μg·mL -1 .
[0083] 3. According to the volume ratio of core layer solution to shell layer solution of 1:1, the shell layer solution and core layer solution were respectively loaded into two 10mL syringes, and coaxial needles were installed. The core layer needle selected here was No. 22, and the shell layer needle was No. 17. The positive high-voltage contact clip was connected to the metal needle, and the negative high-voltage contact clip was connected to the receiver. The aluminum foil fixed on the receiver was used as the receiving device. The power supply, spinning distance, spray speed and other parameters were controlled. Through the electrospinning technology, a pH-sensitive electrospinning nanofiber membrane loaded with enoxacin with a core-shell structure was prepared.
[0084] The conditions of the electrospinning technology are: positive voltage of 10 kV, negative voltage of 1 kV, the distance between the needle tip and the receiving device is 10 cm, the ambient temperature is 25±5°C, the ambient humidity is 30±10%, and the injection speed of the core / shell injection pump is 0.03 / 0.09 mm / min.
[0085] 4. The obtained pH-sensitive nanofiber membrane loaded with enoxacin was dried in a light-proof vacuum to remove the residual solvent.
[0086] Comparative Example 1.5
[0087] A pH-sensitive coaxial nanofiber membrane loaded with enoxacin, the preparation method comprising the following steps:
[0088] 1. Weigh an appropriate amount of ethyl cellulose (EC), add methanol, stir to dissolve, and prepare an ethyl cellulose (EC) solution with a concentration of 8% (w / v%). Weigh an appropriate amount of Eudragit L100, mix it with the fixed ratio ethyl cellulose (EC) solution to make its concentration 15% (w / v%), stir to dissolve, and obtain a uniform solution as the shell solution for spinning.
[0089] In the obtained shell solution, the concentration of ethyl cellulose (EC) is 8% (w / v%) and the concentration of Eudragit L100 is 15% (w / v%) by mass volume percentage.
[0090] 2. Weigh an appropriate amount of ethyl cellulose (EC) and the raw material enoxacin and add them to methanol. Stir on a magnetic stirrer until they are completely dissolved to prepare an EC solution with a concentration of 4% (w / v%) as the core layer solution.
[0091] In the obtained core layer solution, the concentration of ethyl cellulose (EC) was 4% (w / v%) and the concentration of enoxacin was 6.00 μg·mL -1 .
[0092] 3. According to the volume ratio of core layer solution to shell layer solution of 1:1, the shell layer solution and core layer solution were respectively loaded into two 10mL syringes, and coaxial needles were installed. The core layer needle selected here was No. 22, and the shell layer needle was No. 17. The positive high-voltage contact clip was connected to the metal needle, and the negative high-voltage contact clip was connected to the receiver. The aluminum foil fixed on the receiver was used as the receiving device. The power supply, spinning distance, spray speed and other parameters were controlled. Through the electrospinning technology, a pH-sensitive electrospinning nanofiber membrane loaded with enoxacin with a core-shell structure was prepared.
[0093] The conditions of the electrospinning technology are: positive voltage is 18 kV, negative voltage is 1 kV, the distance between the needle tip and the receiving device is 10 cm, the ambient temperature is 25±5°C, the ambient humidity is 30±10%, and the injection speed of the core / shell injection pump is 0.03 / 0.09 mm / min.
[0094] 4. The obtained pH-sensitive nanofiber membrane loaded with enoxacin was dried in a light-proof vacuum to remove the residual solvent.
[0095] Comparative Example 1.6
[0096] A pH-sensitive coaxial nanofiber membrane loaded with enoxacin, the preparation method comprising the following steps:
[0097] 1. Weigh an appropriate amount of ethyl cellulose (EC), add methanol, stir to dissolve, and prepare an ethyl cellulose (EC) solution with a concentration of 8% (w / v%). Weigh an appropriate amount of Eudragit L100, mix it with the fixed ratio ethyl cellulose (EC) solution to make its concentration 15% (w / v%), stir to dissolve, and obtain a uniform solution as the shell solution for spinning.
[0098] In the obtained shell solution, the concentration of ethyl cellulose (EC) is 8% (w / v%) and the concentration of Eudragit L100 is 15% (w / v%) by mass volume percentage.
[0099] 2. Weigh an appropriate amount of ethyl cellulose (EC) and the raw material enoxacin and add them to methanol. Stir on a magnetic stirrer until they are completely dissolved to prepare an EC solution with a concentration of 4% (w / v%) as the core layer solution.
[0100] In the obtained core layer solution, the concentration of ethyl cellulose (EC) was 4% (w / v%) and the concentration of enoxacin was 6.00 μg·mL -1 .
[0101] 3. According to the volume ratio of core layer solution to shell layer solution of 1:1, the shell layer solution and core layer solution were respectively loaded into two 10mL syringes, and coaxial needles were installed. The core layer needle selected here was No. 22, and the shell layer needle was No. 17. The positive high-voltage contact clip was connected to the metal needle, and the negative high-voltage contact clip was connected to the receiver. The aluminum foil fixed on the receiver was used as the receiving device. The power supply, spinning distance, spray speed and other parameters were controlled. Through the electrospinning technology, a pH-sensitive electrospinning nanofiber membrane loaded with enoxacin with a core-shell structure was prepared.
[0102] The conditions of the electrospinning technology are: positive voltage of 22 kV, negative voltage of 1 kV, distance between needle tip and receiving device of 10 cm, ambient temperature of 25±5°C, ambient humidity of 30±10%, and injection speed of core / shell injection pump of 0.03 / 0.09 mm / min.
[0103] 4. The obtained pH-sensitive nanofiber membrane loaded with enoxacin was dried in a light-proof vacuum to remove the residual solvent.
[0104] Comparative Example 2
[0105] A pH-sensitive uniaxial nanofiber membrane loaded with enoxacin, the preparation method comprising the following steps:
[0106] 1. Weigh an appropriate amount of ethyl cellulose (EC), add methanol, stir to dissolve, and prepare an ethyl cellulose (EC) solution with a concentration of 8% (w / v%). Weigh an appropriate amount of Eudragit L100, mix it with a fixed ratio of ethyl cellulose (EC) solution to make its concentration 15% (w / v%), stir to dissolve, and obtain a uniform solution as the spinning solution.
[0107] In the obtained spinning solution, the concentration of ethyl cellulose (EC) is 8% (w / v%) and the concentration of Eudragit L100 is 15% (w / v%) by mass volume percentage.
[0108] 2. Weigh an appropriate amount of the raw material enoxacin and add it to methanol. Stir on a magnetic stirrer until it is completely dissolved to prepare an enoxacin solution with a concentration of 6.00 μg mL -1 , and added it into the spinning solution, and ultrasonicated for 10 minutes to remove the bubbles.
[0109] 3. Pour the prepared spinning solution into a 10mL syringe and install a No. 20 stainless steel needle. Insert the syringe into the bayonet of the push pump and adjust the position of the slider to fix it. Connect the positive high-voltage contact clip to the metal needle and the negative high-voltage contact clip to the receiver. Use the aluminum foil fixed on the receiver as the receiving device, control the power supply, spinning distance, and spray speed, and prepare a pH-sensitive uniaxial electrospinning nanofiber membrane loaded with enoxacin through electrospinning technology.
[0110] The conditions of the electrospinning technology are: positive voltage is 14 kV, negative voltage is 1 kV, the distance between the needle tip and the receiving device is 10 cm, the ambient temperature is 25±5°C, the ambient humidity is 30±10%, and the injection speed of the injection pump is 0.15 mm / min.
[0111] 4. The obtained pH-sensitive enoxacin-loaded uniaxial nanofiber membrane is dried in a light-proof vacuum to remove the residual solvent.
[0112] Example 2 Detection of pH-sensitive coaxial nanofiber membrane loaded with enoxacin
[0113] 1. Morphological analysis of electrospun nanofiber membranes
[0114] Use aluminum foil to collect an appropriate amount of fibers, cut them into appropriate sizes and stick them on the conductive glue, and spray them with gold under the protection of inert gas. Place the nanofiber membrane in a phosphate buffer solution with a pH value of 7.4, take it out after 48 hours and dry it in a vacuum drying oven. After drying, cut the nanofiber membrane into appropriate sizes and stick them on the conductive glue, and spray them with gold under the protection of inert gas. Use a scanning electron microscope to observe the surface morphology of the fiber, and set the acceleration voltage to 5kV. After obtaining the fiber photo, use Image J software to measure and calculate the fiber diameter in the figure, and draw the following. Figure 3 Fiber diameter distribution histogram shown in (b).
[0115] The EC solutions of different concentrations prepared in Example 1 and Comparative Examples 1.1, 1.2 and 1.3 were used as core layer solutions, and EC concentration of 8% and Eudragit L100 concentration of 15% were used as shell layer solutions for electrospinning. The obtained nanofiber membranes were observed using a scanning electron microscope. Figure 1 As shown in the figure, all the formulations can be used to prepare nanofiber membranes by electrospinning. Figure 1 (a) It can be seen that under the same process parameters, when the viscosity of the core layer spinning solution is low, droplets will appear and the fibers will be uneven in thickness. Figure 1 The fibers in (b) have a smooth appearance and uniform diameter, and no droplets or beaded fibers appear, indicating a good spinning state. However, when the viscosity of the core solution is high, Figure 1 (d) The fiber thickness is uneven. When the viscosity of the nuclear layer solution is too high, the fiber diameters will vary greatly and the appearance will be rough due to the failure to fully differentiate and elongate. Therefore, the nuclear layer solution EC concentration of 4% was selected for the experiment.
[0116] 2. Confirmation of the coaxial structure of electrospun nanofiber membrane
[0117] Use a transmission electron microscope to photograph coaxial nanofibers and confirm their coaxial structure. Paste the copper mesh on aluminum foil and use the aluminum foil to receive the fibers. Stop the instrument after receiving for 5 seconds and peel off the copper mesh on the aluminum foil without damaging the fibers as much as possible. Spray gold on the fiber membrane surface on the copper mesh and place it in the instrument to observe and record the results.
[0118] Depend on Figure 4 According to the preparation method in Example 1, (a) the shell diameter is 647nm, the core diameter is 220nm; (b) the shell diameter is 635nm, and the core diameter is 208nm. It can be seen that coaxial electrospinning can prepare nanofibers with a core-shell structure, and when the fiber diameter changes, the core diameter also changes accordingly, which can always ensure the existence of the coaxial structure. Therefore, although the diameter of each fiber in the coaxial nanofiber membrane prepared by the same preparation method may be different, they are all core-shell structures and have similar release behaviors.
[0119] 3. Analysis of drug release behavior
[0120] The in vitro release experiment was conducted in a constant temperature shaker using the shake bottle method. Buffer solutions of pH 4.5, pH 5.5, pH 6.0, pH 6.5 and pH 7.4 were used as dissolution media. 30 mL of the solution was added to a stoppered conical flask, and an appropriate amount of the nanofiber membrane prepared in Example 1 was weighed and placed therein. The conical flask was placed in a constant temperature shaker at a shaking speed of 100 r·min. -1 , the temperature was 37°C. 1 mL was taken with a syringe at 1, 2, 4, 6, 8, 12, 24, and 48 h, respectively, and filtered through a 0.22 μm filter membrane. The absorbance of the sample was measured at 262 nm using an ultraviolet spectrophotometer to calculate the cumulative release rate.
[0121] The in vitro release experiment of nanofiber membranes was used to investigate the release of the model drug enoxacin in the solution in the fiber membranes and simulate the release of the drug at the wound site. Figure 5 These are the release results of the coaxial nanofiber membrane prepared in Example 1 in buffer solutions of five pH values.
[0122] It can be clearly seen from the figure that when the pH value of the release medium is 4.5, 5.5 and 6.0, enoxacin is basically not released, and the release amount within 48 hours is less than 3%. The small amount of drug release may be caused by the breakage of individual fibers, which directly exposes the drug loaded in the core layer to the release medium.
[0123] like Figure 5 As shown in the figure, when the pH value of the release medium is 6.5 and 7.4, there is no burst release of enoxacin in the early stage, indicating that loading the drug in the core layer can solve the problem of burst release of the uniaxial nanofiber membrane. The final cumulative release of enoxacin in 48 hours can reach about 80%. This may be because some enoxacin is electrospun together with water-insoluble ethyl cellulose, making it difficult to release.
[0124] It can be seen that the coaxial nanofiber membrane prepared by electrospinning technology is pH-sensitive and only released at the wound site, which can minimize the adverse reactions caused by drugs. At the same time, it can promote wound healing and improve the speed and quality of wound repair.
[0125] 4. Water vapor transmission rate analysis
[0126] The wound dressing needs to have appropriate water permeability and air permeability to keep the wound surface in a relatively moist environment. The experimental results of the water vapor permeability of the coaxial nanofiber membrane prepared in Example 1 are as follows: Figure 6 As shown in Figure 2, the water vapor permeability of medical tape is 0.170±0.007g·cm -2 ·d -1 The water vapor permeability of Band-aids is 0.225±0.006g·cm -2 ·d-1 The water vapor permeability of medical gauze is 0.275±0.009g·cm -2 ·d -1 The water vapor permeability of the coaxial nanofiber membrane (CNM) prepared in Example 1 was 0.235±0.003 g·cm -2 ·d -1 The water vapor permeability of the coaxial nanofiber membrane is slightly lower than that of the uniaxial nanofiber membrane prepared in Comparative Example 2 (the water vapor permeability of the uniaxial nanofiber membrane prepared in Comparative Example 2 is 0.240±0.009 g·cm -2 ·d -1 ), which may be due to the existence of its coaxial structure, making the porosity smaller than that of the uniaxial nanofiber membrane. However, the water vapor permeability is still in the optimal permeability range of wound dressings, 0.20-0.25g·cm -2 ·d -1 It is more suitable as wound dressing than medical tape and medical gauze.
[0127] 5. Water retention capacity analysis
[0128] The dried fiber membrane prepared in Example 1 was cut into the same size and its mass was accurately weighed. The fiber membrane was placed in 5 mL of distilled water and taken out at 1, 2, 4, 6, 8, 12, 24, and 48 h. The excess water on the surface of the fiber membrane was absorbed with filter paper and then weighed. The water absorption rate was calculated as follows:
[0129] W=(W1-W0) / W0×100%
[0130] W0 is the mass of the nanofiber membrane when it is dry, and W1 is the mass of the nanofiber membrane after absorbing water at different time points. A good water absorption rate can also slow down the evaporation rate of water and keep the wound moist. Studies have shown that when the wound surface is kept in a moist environment, it can promote the shedding of necrotic tissue and stimulate the proliferation of fibroblasts. At the same time, the moist state can promote the migration of keratinocytes better than the dry state, providing a good wound healing environment.
[0131] The water absorption rate of the fiber membrane was calculated at each time point. Figure 7 As shown. After 48 hours, the water absorption rate of the coaxial nanofiber membrane reached 209.69±2.54%. From the experimental results, it can be seen that the water absorption rate of the coaxial fiber membrane can meet the demand for absorbing wound exudate. Example 3 Application of pH-sensitive coaxial nanofiber membrane loaded with enoxacin as wound dressing in promoting wound healing
[0132] SD male rats were selected for the experiment, 5 in each group, and anesthetized with chloral hydrate (10%) injected intraperitoneally at a dose of 3.5 mL kg -1. The rats were fixed on a mouse board, and the hair on the back was first removed with a razor, and then the fine hair was removed with a depilatory cream. The metal burn method was used to create models on the left and right sides of the rat's dorsal spine. A metal rod with a diameter of 1 cm was heated in a constant temperature water bath at 95°C for 1 minute to allow it to be heated evenly. The metal rod was then placed on the skin of the rat's surgical area with the same force for 12 seconds. After each modeling, the metal rod was cooled to the temperature before modeling before the next heating to ensure that the experiment was parallel. 24 hours after modeling, the wound tissue sections were taken for staining to confirm the degree of burns in the modeling area.
[0133] Healing status of burn model: Figure 8 The results show that the drug-loaded nanofiber membrane has a promoting effect on wound healing in the burn model. The commercially available enoxacin cream, the uniaxial drug-loaded nanofiber membrane (MNM) prepared in Comparative Example 2, and the coaxial drug-loaded nanofiber membrane (CNM) prepared in Example 1 were used as wound dressings, and the wound area was recorded on the 1st, 4th, 8th, 14th, and 21st days. Figure 8 (a) is shown. Figure 8 In (b), the red part is the wound area, and the green part is the healed wound area. Figure 8 (c) is the wound area histogram. Figure 8 As shown in the figure, the scald area of rats in each group continued to shrink with time. During the whole process of wound healing, the healing speed of the drug-loaded nanofiber membrane group was faster than that of the blank group and the commercial cream group. The effects of the two groups of nanofiber membranes were better than those of the other groups. It is speculated that the nanofiber membranes have a larger porosity, better water absorption rate and water vapor permeability, which can maintain the relative moisture of the wound surface and promote wound healing. At the same time, the nanofiber membrane itself presents a spatial reticular structure, which is very similar to the structure of the extracellular matrix and can play the same role, serving as a scaffold for keratinocyte migration and adhesion, achieving the effect of promoting skin re-epithelialization. Both uniaxial and coaxial drug-loaded nanofiber membranes can promote wound healing, but on the 21st day, the wound healing condition of the coaxial drug-loaded nanofiber membrane group was better than that of the uniaxial drug-loaded nanofiber membrane. This may be because under the same drug loading, the coaxial nanofiber membrane uses more excipients and has more fibers that can serve as a scaffold for cell adhesion and proliferation.
[0134] The nanofiber membrane prepared by electrospinning technology can not only cover the wound surface to provide physical protection for the wound, but also be permeable to water and air, and have a similar structure to the extracellular matrix, thereby achieving the effect of promoting wound healing.
[0135] Masson staining: Masson staining is performed on the wound site after healing. The healing process is judged by the morphology of collagen fibers in the wound. Paraffin sections are dewaxed, immersed in potassium dichromate for more than 12 hours, and then in hematoxylin solution. The sections are then stained with the corresponding staining solutions. After each step, they are washed with water. The sections are washed in anhydrous ethanol and then transparently sealed. Observe and record with a microscope, and analyze and process the pictures.
[0136] like Figure 8-1 As shown, on the 4th day after the scald, it was observed that obvious inflammatory cell infiltration appeared in the tissue sections of the four groups, collagen fibers were broken and necrotic, and the skin structure was obviously destroyed. On the 8th day after the scald, it was observed that the inflammatory cell infiltration phenomenon of the uniaxial nanofiber membrane group prepared in Comparative Example 2 and the coaxial nanofiber membrane group prepared in Example 1 was significantly reduced, and there were still a large number of inflammatory cells in the blank control group and the ointment group. Except for the blank control group, the other three groups can be observed to have begun to rebuild the epidermis. On the 14th day after the scald, it was observed that the epidermal cells of the ointment group and the preparation group were arranged neatly, and accessory organs appeared. Inflammatory cells were still present in the blank control group. On the 21st day after the scald, the skin structure of the ointment group, the uniaxial nanofiber membrane group prepared in Comparative Example 2, and the coaxial nanofiber membrane group prepared in Example 1 had returned to normal, the epidermal structure was intact, and the collagen fibers were arranged in order, among which the fiber state of the coaxial nanofiber membrane group prepared in Example 1 was closer to normal skin. The collagen fibers in the blank control group were not arranged neatly, and were still in the process of epidermal reconstruction.
[0137] VEGF and CD31 histochemical detection: Take tissue sections on the 8th and 21st day of wound healing, dewax to water, repair antigens and wash, and then wash in PBST for 5 minutes. Then block the tissue sections with 3% BSA for 30 minutes. Add primary and secondary antibodies (HRP labeled) and wash in PBST. Use DAB solution to develop tissue color on the sections, and wash with water after observing the desired effect. Then counterstain the cell nucleus, return to blue, and the sections are transparent in xylene, and finally perform the sealing operation.
[0138] VEGF is vascular endothelial growth factor, also known as angiotropin. Its biological characteristics are mainly manifested in two aspects: one is to promote the division and proliferation of vascular endothelial cells, thereby promoting angiogenesis; the other is to increase the permeability of microvessels and specifically bind to its vascular endothelial cell receptors. Therefore, by detecting the content of VEGF in tissue sections, the situation of angiogenesis can be reflected. Fig. 9 It can be seen that on the 8th day after the burn, the VEGF levels in the four groups were relatively high, and the blank control group had the least positive results, proving that the nanofiber membrane can promote the proliferation of vascular endothelial cells, thereby accelerating the speed of wound repair. On the 21st day after the burn, the positive results in the blank control group increased compared with the 8th day, and the wound was still in the process of repair.
[0139] CD31 is a platelet endothelial cell adhesion molecule, a marker that is widely used in characterization methods. It is mainly found on the surface of platelets, endothelial cells, etc., and can be used to color new blood vessels. When the skin is burned or scalded, a crucial link in the angiogenesis process is the aggregation of endothelial cells at the wound. Endothelial cells provide more nutrients to the wound in the form of new blood vessels, transport more oxygen, and produce biologically active compounds, thereby accelerating wound healing. The earlier the new blood vessels appear, the earlier the process of wound repair begins.
[0140] like Fig.10 As shown, on the 8th day after the scald, high CD31 expression was observed in all four groups, and the CD31 expression in the ointment group and the uniaxial and coaxial drug-loaded nanofiber membrane groups was significantly higher than that in the blank control group, among which the effect of the coaxial nanofiber membrane was particularly significant. This shows that the structure of the nanofiber membrane can promote the expression of CD31 in the early stage of wound healing, thereby improving the speed and quality of wound repair. On the 21st day after the scald, the CD31 positive results in the ointment group and the uniaxial and coaxial nanofiber membrane groups were significantly lower than those on the 8th day, indicating that the peak of wound repair had been reached before, while the CD31 expression in the blank control group was higher on the 21st day than on the 8th day, indicating that the blank control group reached its peak of repair later than the other three groups.
Claims
1. A pH-sensitive coaxial electrospun nanofiber membrane loaded with enoxacin, characterized in that: The electrospinning nanofiber membrane consists of a shell layer and a core layer, wherein the shell layer contains ethyl cellulose and Eudragit L100, and the core layer contains ethyl cellulose and enoxacin, and is prepared by electrospinning technology.
2. The method for preparing a pH-sensitive electrospun nanofiber membrane loaded with enoxacin according to claim 1, characterized in that: The steps include: 1) Dissolve ethyl cellulose EC and Eudragit L100, stir evenly, and remove bubbles by ultrasound to obtain a shell solution; 2) Dissolve ethyl cellulose EC and the raw material drug enoxacin in methanol, stir evenly, and remove bubbles by ultrasound to obtain a core layer solution; 3) The shell layer solution and the core layer solution are respectively loaded into two syringes, and a coaxial needle is installed, and the positive high voltage contact clip is connected to the metal needle, and the negative high voltage contact clip is connected to the receiver, and the aluminum foil fixed on the receiver is used as a receiving device, and the power supply, spinning distance, and spray speed are controlled, and a pH-sensitive coaxial electrospinning nanofiber membrane loaded with enoxacin having a core-shell structure is prepared by electrospinning technology; 4) The obtained pH-sensitive coaxial electrospun nanofiber membrane loaded with enoxacin was dried in a light-proof vacuum to remove the residual solvent.
3. The preparation method according to claim 2, characterized in that: In step 1), the shell solution has an ethyl cellulose EC concentration of 8% and an Eudragit L100 concentration of 15%.
4. The preparation method according to claim 2, characterized in that: In step 2), the core layer solution has an ethyl cellulose EC concentration of 2-8% and an enoxacin concentration of 5.00-7.00 μg·mL -1 .
5. The preparation method according to claim 4, characterized in that: In step 2), the core layer solution has an ethyl cellulose EC concentration of 4% and an enoxacin concentration of 6.00 μg·mL -1 .
6. The preparation method according to claim 2, characterized in that: In step 3), the volume ratio of the core layer solution to the shell layer solution is 1:1-4.
7. The preparation method according to claim 6, characterized in that: In step 3), the volume ratio of the core layer solution to the shell layer solution is 1:
1.
8. The preparation method according to claim 2, characterized in that: In step 3), the needle for the core layer solution is 22 gauge, and the needle for the shell layer solution is 17 gauge.
9. The preparation method according to claim 2, characterized in that: In step 3), the conditions of the electrospinning technology are: positive voltage is 14 kV, negative voltage is 1 kV, the distance between the needle tip and the receiving device is 10 cm, the ambient temperature is 25±5°C, the ambient humidity is 30±10%, and the injection speed of the core layer / shell layer injection pump is 0.03 / 0.09 mm / min.
10. Use of the pH-sensitive coaxial electrospun nanofiber membrane loaded with enoxacin as claimed in claim 1 as a wound dressing.
Citation Information
Patent Citations
Enoxacin ocular sustained release gelata and preparation thereof
CN100563657C
An enoxacin acrylone derivative, its preparation method and application
CN112824406B
Cited By
Preparation method of pH developing antibacterial nanofiber wrap yarn
CN120401086A